Health Insurance as Economic Stimulus? Evidence from Long-Term Care Jobs - Martin Hackmann; Jörg Heining; Roman Klimke; Maria Polyakova; Holger Seibert (CESifo GmbH, 2025)
We leverage decades of administrative data and quasi-experimental variation in the introduction of universal long-term care (LTC) insurance in Germany in 1995 to examine whether health insurance expansions can stimulate local economies. We find that the LTC insurance rollout led not only to sizeable growth of the target LTC sector, but also to an aggregate fall in unemployment and an increase in the labor force participation. Quantitatively, a 10 percentage point increase in the share of insured LTC patients led to 4 more nursing home workers per 1,000 individuals age 65 and older (12% increase). Wages did not rise in the LTC sector or other sectors of the economy. The quality of newly hired nursing home workers declined, but this had no negative effect on old-age life expectancy. Overall, the insurance expansion brought lower-skilled workers into new jobs rather than reallocating workers away from other productive sectors. Our marginal value of public funds (MVPF) analysis suggests that the reform paid for itself when taking the positive fiscal externalities in the labor market into account. To understand which market primitives underpin our findings and to inform the external validity of our results, we develop and estimate a general model of labor markets with product-market subsidies in the presence of wedges, such as income taxes. Our model simulations show that the aggregate welfare effects of insurance expansions are theoretically ambiguous and depend centrally on the magnitude of frictions in input markets.
Keywords: D58; H51; I13; I31; I38; J14; J23; J64; 330; health insurance expansion; long-term care; aggregate economic impact; labor market effects; stimulus; moral hazard; welfare analysis